Acalabrutinib Plus Bendamustine-Rituximab in Untreated Mantle Cell Lymphoma - Wang, Michael; Salek, David; Belada, David; Song, Yuqin; Jurczak, Wojciech; Kahl, Brad S; Paludo, Jonas; Chu, Michael P; Kryachok, Iryna; Fogliatto, Laura; Cheah, Chan Y; Morawska, Marta; et al. (Journal of clinical oncology, 2025)
PURPOSE: The combination of the Bruton tyrosine kinase inhibitor ibrutinib with bendamustine-rituximab for first-line treatment of mantle cell lymphoma (MCL) prolonged progression-free survival (PFS), but without improvement in overall survival (OS), likely because of toxicity. Acalabrutinib was shown to be efficacious and less toxic than ibrutinib in a head-to-head trial in chronic lymphocytic leukemia and therefore might lead to better outcomes in MCL. METHODS: Patients 65 years and older with previously untreated MCL received acalabrutinib (100 mg twice daily) or placebo (until disease progression or unacceptable toxicity), plus six cycles of bendamustine (90 mg/m2 once daily; days 1 and 2) and rituximab (375 mg/m2 as a single dose; day 1) followed by rituximab maintenance in responding patients for 2 years. Crossover to acalabrutinib at disease progression was permitted. The primary end point was PFS per the independent review committee; overall response rate and OS were secondary end points. RESULTS: In total, 598 patients were randomly assigned, with 299 in each arm. At a median follow-up of 49.8 months using the reverse Kaplan-Meier method, the median PFS was 66.4 months in the acalabrutinib arm and 49.6 months in the placebo arm (hazard ratio [HR], 0.73 [95% CI, 0.57 to 0.94]; P = .0160). Benefit was seen across all subgroups, including those with high-risk features. Overall response/complete response rates were 91.0%/66.6% and 88.0%/53.5% in the acalabrutinib and placebo arms, respectively. OS was not significantly different (HR, 0.86 [95% CI, 0.65 to 1.13]; P = .27). Grade 3 or greater adverse events were reported in 88.9% and 88.2% in the acalabrutinib and placebo arms, respectively. CONCLUSION: The combination of acalabrutinib with bendamustine-rituximab significantly improved PFS. Clinical benefit of acalabrutinib with bendamustine-rituximab was achieved with manageable toxicity.
Keywords: Bendamustine Hydrochloride; Rituximab; Lymphoma, Mantle-Cell; Male; doba přežití bez progrese choroby; Antineoplastic Combined Chemotherapy Protocols; pyraziny; lymfom z plášťových buněk; benzamidy; Aged; mužské pohlaví; senioři; Benzamides; rituximab; dvojitá slepá metoda; senioři nad 80 let; lidé; ženské pohlaví; Humans; protokoly protinádorové kombinované chemoterapie; Aged, 80 and over; bendamustin hydrochlorid; Pyrazines; Double-Blind Method; Female; Progression-Free Survival